Yttrium Oxide (Y2O3) as a Pulse Initiator in a Mode-Locking Erbium-Doped Fiber Laser - N. F. Zulkipli; A. R. Muhammad; M. Batumalay; A. H. A. Rosol; A. Altuncu; F. E. Durak; M. F. Ma’mun; S. W. Harun (Photonics, 2022)
Mode-locking is an ultra-short pulse laser generation technique. The range of pulse duration may vary from picoseconds to femtoseconds. Yttrium Oxide (Y2O3) based saturable absorber (SA) was appropriately revealed in the mode-locked method within the 1.55-micron regime. Y2O3 is perfect for strength, melting point, and chemical stability and can be used as a laminated insulator due to its properties. Moreover, Y2O3 also owns broadband service, switching speed, and engineering features. The Y2O3-PVA film was produced by combining the 50 mg Y2O3 powder into a 50 mL polyvinyl alcohol (PVA) solution and stirring it at room temperature for about 24 h. A mode-locked pulse was recorded with the integrated Y2O3-PVA SA in the erbium-doped fiber laser (EDFL) cavity, and the output spectrum optical spectrum analyzer displayed was around 1560.66 nm. In addition to the sustained mode-locked pulse, a nearly constant repetition rate of 1.01 MHz at a specific pump power begins from 175.87 mW to 228.04 mW while the pulse duration is 4.15 ps. Lastly, the mode-locked pulse had been evaluated, which showed the peak power started from 4.94 kW to 6.07 kW.